Impact of demographics on volunteering patterns in UUM - Nur Alia Zamzuri; Mohd Adib Abd Muin (Penerbit Universiti Kebangsaan Malaysia, 2024)
During the COVID-19 pandemic, an increase in psychological symptoms such as anxiety, perceived stress, and depression was observed in the general population. University students, who are already at a higher risk for mental health disorders even under normal circumstances, have been the subject of research to understand the impact of demographics on volunteering patterns at Universiti Utara Malaysia (UUM). This study utilised primary data collected through a survey and employed content analysis to examine the research findings. The survey participants were drawn from the UUM students. Based on the collected demographic data, the analysis revealed a relationship between volunteerism and the mental health well-being of UUM students. The implications of this research suggest that UUM and similar institutions should develop more volunteer programs. Such initiatives could foster a supportive environment that enhances students' mental health and well-being, thereby contributing to the cultivation of a new generation of successful volunteers with a positive impact on both the students themselves and the broader society.